The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ijscr.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Modified Masquelet technique using allogeneic umbilical cord-derived mesenchymal stem cells for infected non-union femoral shaft fracture with a 12 cm bone defect: A case report

Abstract: HighlightsA case of infected non-union fracture with critical-sized bone defect.Modified Masquelet technique was used to overcome the defect.The addition of allogenic UC-MSCs, BMP-2 and hydroxyapatite encourages healing.This technique may serve as an effective way to overcome large defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
2
22
0
3
Order By: Relevance
“…Stem cells from other sources might also be of value. For example, a case report on human CSD reconstruction with the Masquelet technique combined umbilical-cord-derived MSCs, BMP2, and hydroxyapatite (Dilogo, Primaputra, Pawitan, & Liem, 2017). Successful bone healing was observed with the formation of new bone in 12-cm defects (Dilogo et al, 2017).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Stem cells from other sources might also be of value. For example, a case report on human CSD reconstruction with the Masquelet technique combined umbilical-cord-derived MSCs, BMP2, and hydroxyapatite (Dilogo, Primaputra, Pawitan, & Liem, 2017). Successful bone healing was observed with the formation of new bone in 12-cm defects (Dilogo et al, 2017).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Previously, we administered allogeneic UC-MSCs for infected non-union femoral shaft fracture with a 12 cm bone defect. 15 There was a reduction of VAS, from a median of 1 (0-6) to 0 (0-4), and increase in mean LEFS/DASH of 56.25 ± 10.71 to 65 ± 22.72 in one year of follow-up. In an animal model, Qu et al found that the administration of UC-MSCs resulted in disappearance of fracture line at eight weeks.…”
Section: Discussionmentioning
confidence: 82%
“…These factors enhance migration and recruitment of osteoprogenitor cells (osteoblasts) to the implantation site and assists in upregulation of cell proliferation and differentiation. 15,35 Besides, these factors also aid in angiogenesis, in order to fulfill oxygen and nutritional requirements during fracture healing. 35 In comparison from other types of stem cells, MSC poses a shallow risk when implanted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In Cipto Mangunkusumo Hospital (RSCM), other studies, which are using stem cells are ongoing, such as studies on osteoarthritis, spinal cord injury, 3 rd degree burn wound, and near blind glaucoma. For the future, stem cell therapy studies for other various conditions, which have been proven in animals, are being established; therefore, stem cell therapy and stem cell related products might become an option for ESRD in the future.…”
mentioning
confidence: 99%